Analisis Kontekstual Nilai-Nilai Agama dalam Materi Ekosistem pada Pembelajaran IPAS di Madrasah Ibtidaiyah - Yuniarsih, Krisma; Fatonah, Siti (Balai Diklat Keagamaan Bandung, 2025)
Internalisation of religious values in learning materials for students is critical for producing generations that are aligned with national educational aims. The study aims to examine the religious values included in ecosystem material used in Natural and Social Sciences (IPAS) education at Madrasah Ibtidaiyah. This study employs a descriptive qualitative approach with a document analysis technique. Data were gathered from the grade 5 IPAS textbook, the Merdeka Curriculum Guide, and Islamic literature including the Qur'an, hadith, and pertinent scientific papers. The investigation was conducted by identifying ecological features such as food chains, living creature interactions, and environmental balance that are related to religious principles. The results showed that ecosystem material can be used to instill students' understanding of the importance of maintaining the balance of the ecosystem as a form of worship and responsibility for God's creation. Ecosystem material discusses the relationship between living things and their environment, has great potential to be integrated with Islamic values, such as the balance of nature (mizan), cooperation (ta'awun), human responsibility as khalifah, and compassion for living things (rahmah). This study recommends the development of teaching materials that explicitly link ecosystem concepts with Islamic values to create more meaningful learning.Keywords: ecosystem; religious values; IPAS; independent curriculum; integrative education